Prediction of spiralling in BTA deep-hole drilling: estimating the system's eigenfrequencies - Gero Szepannek; Nils Raabe; Oliver Webber; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
One serious problem in deep-hole drilling is the formation of a dynamic disturbance called spiralling which causes holes with several lobes. Since such lobes are a severe impairment of the bore hole quality the formation of spiralling has to be prevented. Gessesse et al. [2] explain spiralling by the coincidence of bending modes and multiples of the rotation frequency. They derive this from an elaborate finite elements model of the process. In online measurements we detected slowly changing frequency patterns similar to those calculated by Gessesse et al. We therefore propose a method to estimate the parameters determining the change of frequencies over time from spectrogram data. This significantly simplifies the explanation of spiralling for practical applications compared to finite elements models which have to be correctly modified for each machine and tool assembly. It turns out that this simpler model achieves to explain the observed frequency patterns quite well. We use this for estimating the variation of the frequencies as good as possible. This opens up the opportunity to prevent spiralling by e.g. changing the rotary frequency.
Keywords: 519